FPGA implementation of a linear module for the estimation of electrical parameters for a photovoltaic system (PVS) - Lozano-Rivera, Clevis (2020)
This papers presents the analysis and evaluation of the FPGA implementation of a linear adaptive model for the estimation of linearized electrical parameters. These parameters may come, for instance, from non linear models required for complex systems’ efficiency monitoring and/or closed control loop, with speed processing needs not feasible for traditional embedded systems (on the order of at least 1 mega-sample per second). The implemented model is composed by a set of equations, that have been derived from an estimation approach based on a typical Euler numeric differential equation solver. In the particular case here presented, the parameters represent the dynamic behavior of a photovoltaic generator panel. The goal of the model is to evaluate the performance of distributed maximum power tracking algorithms, from a single equation that estimates the current-voltage relations. The algorithm is evaluated first using a Register Transfer Level (RTL) Verilog description, and then is tested on a commercial FPGA with data generated from a high level golden model reference. Final validation on integrated circuits Electronic Design Automation (EDA) tools show that the design is not only feasible to be ported to a commercial CMOS technology, but that is efficient in terms of processing speed and power consumption. Such efficiency makes it adequate for the monitoring and control of interconnected solar panels.